The continuum of high ovarian response: a rational approach to the management of high responder patient subgroups. (2nd November 2015) - Gat, Itai; Shlush, Ekaterina; Quach, Kevin; Librach, Clifford L.
Abstract: Ovarian follicular responsiveness to controlled ovarian hyperstimulation (COH) with gonadotropins is extremely variable between individual patients, and even from cycle to cycle for the same patient. High responder patients are characterized by an exaggerated response to gonadotropin administration, accompanied by a higher risk for ovarian hyperstimulation syndrome (OHSS). In spite of its importance, the literature regarding high responders is characterized by heterogeneous classification methodologies. A clear separation should be drawn between risk factors for a high ovarian response and the actual response exhibited by a patient to stimulation. Similarly, it is important to distinguish between high ovarian response and development of clinically significant OHSS. In this article we: (1) review recent publications pertaining to the identification and clinical management of high responders, (2) propose an integrated clinical model to differentiate sub-groups within this population based on this review, and (3) suggest specific protocols for each sub-group. The model is based on a chronological patient assessment in an effort to target treatment based on the specific clinical circumstances. It is our hope that the algorithm we have developed will assist clinicians to supply targeted and precise treatments in order to achieve a favorable reproductive outcome with minimum complications for each patient.